Sharia Economic Ethics in the Utilization of In Vitro Fertilization Technology within the Lavender Marriage Phenomenon - Fajrina Dhia Salsabila; Hasan Syahrizal (IQRAR: Jurnal Akuntansi, Manajemen & Ekonomi Syariah, 2025)
The use of in vitro fertilization (IVF) within lavender marriage arrangements demonstrates how social pressures, the commercialization of reproductive services, and insufficient ethical governance can lead to deviations from the medical purpose of assisted reproductive technologies. This study aims to analyze the practice of IVF in lavender marriages through the lens of sharia economic ethics, particularly the principles of amanah, shiddiq, maslahah, and the protection of lineage. The research employed a descriptive–analytical qualitative method based on a comprehensive literature review of contemporary Islamic jurisprudence, medical ethics, and governance of fertility clinics. The findings indicate that IVF is frequently utilized to construct an artificial image of heteronormative family life, creating moral concerns, psychological risks for children, commercial vulnerabilities, and potential violations of maqashid al-shariah. The implications emphasize the need for strengthened sharia-based regulations in assisted reproductive services and broader social-ethical reform to prevent the misuse of medical technology as a tool for concealing identity or sustaining superficial social legitimacy